The Effect of Digital Game-Based Learning on Improving Students' Social Skills in the Hybrid Education Era - Dewi Pratiwi Sumarni; Budi Santoso (PT. Technology Laboratories Indonesia (TechnoLabs), 2024)
This study investigates the impact of digital game-based learning on the improvement of students' social skills within the context of hybrid education. A quasi-experimental design was used, involving 60 students from Universitas Pendidikan Nusantara, divided into an experimental group (n = 30) and a control group (n = 30). The experimental group engaged in a 6-week game-based learning intervention using the digital game